Communication infrastructure planning for wide area measurement systems in power systems. (1st January 2013) - Shahraeini, Mohammad; Javidi, Mohammad Hossein; Ghazizadeh, Mohammad Sadegh
Smart grid denotes integration of all elements connected to a power grid with a communication infrastructure. In modern power systems, wide area measurement systems (WAMS) are such systems that use communication infrastructure to share their data and information. Recently, WAMS have been a new opportunity that contributes power system operators to receive and process the whole information of the system. State estimation is recognised as the basis of WAMS applications since it provides creditable data for other WAMS applications. In this study, we propose a new approach to design communication infrastructures of power systems. The designed communication infrastructure creates routing paths from installed phasor measurement units to the control centre in order to estimate system states. Simulation results confirm that, in a WAMS implementation, the price of secure, reliable and high-speed communication infrastructure of such a WAMS should be taken into account.